The Professional Criminal (Archives of Criminology, 2002)
The article seeks to sum up all that has been said on the subject of professional criminality in the past half-century. It was never any part of the author’s aim to offer an analysis of contemporary professional crime. He viewed his task in much more modest terms. First of all he presents the origins of professional crime in a historical perspective and adduces the traditional definitions of the phenomenon dating to the first decade of the 20th century. Next he addresses the issue of empirical determination of the scale of professional crime and presents more recent approaches to description of this kind of criminality and attempts to define the concept of professional criminal. In an account with a primarily sociological focus the emphasis is on the origins of professional criminality seen as one of many mechanisms regulating the behavior of individuals.Historical sources indicate that professional criminality made its appearance during the late Middle Ages when feudal social structures were overtaken by a process of disintegration. The rise of this type of crime was made possibile by the materialization of conducive social and economic conditions such as changes in social structure and mass production. Professional crime is a product of modern societies, which employ money and produce surpluses of goods. In primitive societies there are not enough goods in the possession of the average citizen for the professional criminal to make a livelihood from larceny and for this occupation to be viable as one of the forms of organized social activity.Scholars did not discern this problem until the end of the 19th century. The first one to introduce the idea of the professional criminal to the language of criminology, law and sociology was F. Liszt. This was at a time when lawyers, anthropologists and sociologists were engaged in debates and arguments on the subject of repeated criminality and ways of tackling crime of this type. It was then that there came the first definition of professional criminality. There was agreement among many analysts of that period that the most important thing was to recognize that wrongdoers polish their expertise in the art of committing crime and make such activities a permanent source of income. Simultaneously, in the United States there came the beginnings of in-depth studies of social phenomena, including crime, pioneered by the Chicago School. One result of the new investigative approach was the first studies of professional crime, notably Edwin Sutherland’s well-known work The Professional Thief.The traditional definition of the concept of professional criminal derives precisely from this period, that is the first half of the 19th century. Though investigations in Europe and the United States followed a variety of directions the findings with regard to the principal characteristics of professional criminals were substantially similar. The basic characteristic was seen to be the fact that professional criminals earn their living from committing crimes, which means that the time normally devoted to employment is in their case devoted to planning and carrying out criminal activities. A second salient characteristic was possession of the requisite knowledge, skills and experience in the field of criminal activity. Another influence on this kind of career choice is a sense of identification with the criminal world and a hostile attitude to the representatives of law and order although the professional criminal also knows how to deal with them in a crisis situation (e.g. arest).Despite the existence of a host of writings on the subject of professional criminality and agreement among many authors about its principal characteristics, voices questioning the existence of such a category as the professional criminal continue to make themselves heard. The aforementioned works also includes ones whose authors attempted empirical verification of the existence of such a category of criminals and determination of the scale of professional criminality as a social phenomenon. Here investigation encountered obstacles as it was found that the more or less generally accepted definition of professional criminal did not easily lend itself to the process of operationalization. None the less, as a result of research conducted in various countries, in various periods and by diverse methods scholars have succeeded in establishing that professional criminality does exist and is a widespread phenomenon rather than the elite occupation that it might appear to be based on the proposed definitions. Students of the subject suggest that the number of persons meeting the definition (even in its simplest version) should be estimated in thousands rather than double digits.Professional criminality is from a legal point of view a phenomenon of no interest. The commission of a crime by a perpetrator who can be characterized as a professional criminal does not in most cases weigh for anything in determining the degree of criminal responsibility. However, professional crime is of interest as a social phenomenon, which explains why the literature on the subject is dominated by works with a typically sociological approach. Scholarly inquiry revolved around a number of problems which in terms of the intrinsic nature of the phenomenon discussed here are of the essence. Of these the most important are the relationship between professional criminals and their social environment and with the wider community, their attitude to law enforcement agencies, social status, rationalization of their behavior, and the machinery of recruitment to this group.Though the relations between the criminal and the “occupational” group take a diversity of forms, it is those of a normative character which are of overriding significance. It is thanks to the criminal group that he acquires professional criminal status and the group which lays down the system of rulet for the criminal’s social and professional conduct and which forms the natural infrastructure for criminal activity. On the other hand, every criminal is also a member of society to which he is connected by a multiplicity of ties. If he is to function in the community at all normally, even if it is only on the fringes of social life, he has somehow to rationalize his behavior which is, at bottom, directed against society. The most frequent way in which he does this is by questioning the honesty of all other participants in the social situation or by moral disparagement of his victim.There is no agreement among scholars on the question of nature of the professional criminal’s attitude to “normal” society. Some maintain that it is negative, others that it is positive. The former stress the fact that a negative attitude is a simple consequence of employing rationalization mechanisms which place the perpetrator of crimes in a conflict or at best hostility relationship with society. According to the opposite school of thought professional criminals try to maintain the best possible relations with society and are sympathetically disposed towards it since its success and well-being are for them a guarantee of rich pickings. However, there is a special relationship between professional criminals and the representatives of law enforcement. A natural consequence of their chosen career is that they are in a state of permanent conflict with the guardians of law and order. However, conflict does not necessarily mean enmity. Police officers regard the elite of the criminal world with a peculiar kind of respect, especially thieves who do not resort to violence. Though professional criminals treat police officers or prison guards as their adversaries they acknowledge their superiority at the moment of apprehension. They then go out of their way to gain an officer’s favor and will not shrink from attempting bribery and occasionally even passing on information.The normative character of the professional criminal’s relations with the criminal group means that the machinery of recruitment of new members becomes the crux of the matter. On this point, too, researchers’ opinions are divided. There are those who contend that the phenomenon of recruitment exists and that it is the crucial element in the creation of occupational identity and internalization of group norms. The critics of this view readily cite empirical data which indicate that criminals themselves deny the existence of a phenomenon of recruitment and its performance of any kind of regulatory function.The so-called traditional method of defining professional crime, given currency by European legal theorists and American sociologists in the first half of the 19th century, has come under criticism in recent decades. Researcher representing various theoretical schools have gathered empirical evidence that calls in question the existence of a category of professional criminals who make their living solely from crime, specialize in one kind of crime and are closely connected with the criminal world, the latter being their point of reference and source of norms and rules of conduct. The reality seems to be more complicated. Among criminals there are some who are beyond question professionals and specialists in some area of activity but have never belonged to any sort of criminal community. There are also felons who have strong links to criminal groups but engage in a diversity of criminal activity and do not aspire to any form of specialization. It is becoming increasingly frequent to treat the criminal community not as a reference group but as a natural infrastructure for criminal activity. A question that arises in this context concerns the connections between professional crime and organized crime which for years was treated by criminology as a separate and distinct phenomenon. In the crime patterns of recent decades there have also appeared other developments (car theft, cybercrime) with respect to which the traditional method of defining professional crime has proved useless.The questions raised and the doubts voiced have confronted criminology with the necessity of redefining professional criminality. However, if the phenomenon is viewed in a somewhat broader perspective it has to be noted that one of the most important challenges for contemporary criminology might prove to be reorientation of theoretical reflection on the subject of definition and classification of criminal behavior in general and by the same token reorientation of our way of thinking about construction of typology of crime.